Lower genital tract infections in preterm premature rupture of membranes and preterm labor: a case-control study from Vietnam - Quoc Huy Vu Nguyen; Hung Nam Le; Van Anh Ton Nu; Nguyen Dac Nguyen; Minh Tam Le (Journal of Infection in Developing Countries)
Introduction: This study aimed to determine the incidence of lower genital infections and related factors in preterm premature rupture of membranes (PPROM) and preterm labor.